2023
DOI: 10.1007/s10904-023-02878-4
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Micelles with Chiral Diamine-Ru(II) Catalysts for Asymmetric Transfer Hydrogenation of Ketones in Water

Lianpei Zhou,
Peipei Ji,
Xiuwu Wang
et al.

Abstract: Chiral aromatic alcohols with unique structures have attracted wide attention in asymmetric catalysis for decades. In this study, polymeric micelles with chiral diamine-Ru(II) catalysts in the hydrophobic core for asymmetric transfer hydrogenation of ketones affording chiral aromatic alcohols were presented. Firstly, block polymers with (1R,2R)-(+)-1,2-diphenyl ethylenediamine (DPEN) in the branched chain were successfully synthesized by Ring-Opening Metathesis Polymerization (ROMP) using 1,1-dimethylethyl N-(… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…In 2022, Jia et al successfully synthesized a star-shaped thermal responsive polymer 11 via ATRP polymerization (Scheme 11). 49,50 The resulting polymer was immobilized onto a chiral metal–organic catalyst prepared using Ru metal and chiral diamine ligands, with the chiral ligand coordinating with Cu 2+ metal. The research revealed that the interaction between the chiral polymer and Cu 2+ results in the emergence of a chiral amplification phenomenon.…”
Section: Soluble Carrier Loaded Catalystmentioning
confidence: 99%
“…In 2022, Jia et al successfully synthesized a star-shaped thermal responsive polymer 11 via ATRP polymerization (Scheme 11). 49,50 The resulting polymer was immobilized onto a chiral metal–organic catalyst prepared using Ru metal and chiral diamine ligands, with the chiral ligand coordinating with Cu 2+ metal. The research revealed that the interaction between the chiral polymer and Cu 2+ results in the emergence of a chiral amplification phenomenon.…”
Section: Soluble Carrier Loaded Catalystmentioning
confidence: 99%